2021
DOI: 10.3390/transplantology2040042
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Immune Suppression Post-Liver Transplantation: A Review

Abstract: Since the first liver transplantation operation (LT) in 1967 by Thomas Starzl, efforts to increase survival and prevent rejection have taken place. The development of calcineurin inhibitors (CNIs) in the 1980s led to a surge in survival post-transplantation, and since then, strategies to prevent graft loss and preserve long-term graft function have been prioritized. Allograft rejection is mediated by the host immune response to donor antigens. Prevention of rejection can be achieved through either immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…The exact approach to reducing IS in LT patients remains partly unclear and always requires knowledge of the individual patient s risk profile, comorbidities and tolerance to different substances and their adverse effects [47][48][49]. CNIs remain the most important substance, and all patients undergoing RIM in our study were found with reductions in this drug class.…”
Section: Discussionmentioning
confidence: 80%
“…The exact approach to reducing IS in LT patients remains partly unclear and always requires knowledge of the individual patient s risk profile, comorbidities and tolerance to different substances and their adverse effects [47][48][49]. CNIs remain the most important substance, and all patients undergoing RIM in our study were found with reductions in this drug class.…”
Section: Discussionmentioning
confidence: 80%